The Political Aims of Jesus - Oakman, Douglas E. (Book collections on Project MUSE., 2012)
"Amid competing portrayals of the 'cynic Jesus, ' the 'peasant Jesus, ' and the 'apocalyptic Jesus, ' the 'political Jesus' remains a marginal figure. Douglas E. Oakman argues that advances in our social-scientific understanding of the political economy of Roman Galilee, as well as advances in the so-called 'Third Quest' for the historical Jesus, warrant a revival-and a critical revision-of H.S. Reimarus's understanding of Jesus as an instigator of revolutionary change."--Publisher description